The Impact of Interest Rate, Gross Domestic Product, and Debt-To- Income Ratio on Debt Management among University Students - Nuradibah, Mokhtar; Nuraini, Abdullah; Norhafifah, Samsudin; Gary Pen, Siaw Seng (RSIS International, 2026)
The purpose of this study is to examine the impact of interest rate, gross domestic product (GDP), and debt-to- income ratio on debt management practices among students at Universiti Malaysia Sarawak (UNIMAS). The study employs a mixed approach, with primary data collected via structured surveys targeting 300 respondents and secondary data on Malaysia's macroeconomic indicators obtained from the World Bank. Findings reveal that interest rates and GDP have weak, insignificant effects on debt management, while the debt-to-income ratio shows a slightly stronger link. Respondents who compare loan options and manage loans well tend to have lower debt burdens. This suggests personal financial behaviour plays a more crucial role than macroeconomic factors, highlighting the need for financial literacy programs to support responsible borrowing in university communities.